Determination of chlorpyrifos residues in apple (Malus domestica) before and after soaking treatments using solid phase microextraction (SPME) and gas Chromatography mass spectrometry detector (GC-MSD) / Mohd Zudi Mohd Zahari - Mohd Zahari, Mohd Zudi (Faculty of Applied Sciences, 2008)
The residues of chlorpyrifos in apple (Malus domestica) were analyzed by method of solid phase microextraction (SPME) coupled to gas chromatography with mass spectrometry detector (GC-MS). Experiments were carried out to optimize the SPME conditions in order to enhance the fiber performance and obtain high amount of chlorpyrifos extracted. It was found that the optimum SPME condition was extraction temperature of 60o C and extraction time of 20 min. The headspace SPME extraction mode was applied to determine chlorpyrifos residues in apple after being exposed to the pesticides. The effects of soaking treatments using tap water and non toxic solutions namely 10% (w/v) salt solution and 10% (v/v) vinegar solution were investigated with measurement of chlorpyrifos reduction in contaminated apple after treatments were implemented. The results showed that the salt solution was the most effective solution for chlorpyrifos removal at 84.84%, whereas soaking with tap water was found to be the least effective with 66.25% and the reduction of chlorpyrifos residues was 74% using vinegar.